﻿Defensive phragmosis and cathaptosis in Trichoptera larvae - Megan J. Bishoff; Lang Peng; Hao-ming Zang; John C. Morse (Contributions to Entomology)
Phragmosis, or the use of specially modified body parts and associated behaviors to block an opening as defense against predators, is a commonly observed phenomenon in certain ants and termites that block entrances of their subterranean nests with large, flat heads. It has been reported in some beetles and other insects and even in some frogs. Common features of phragmosis in caddisfly larvae include a hard and usually flat body surface, with or without stout spines, and the behavior of fitting that body surface tightly in the opening of its case. A different defensive strategy occurs in snails and case-making larvae of camptosomate leaf beetles (Chrysomelidae: Cryptocephalinae and Lamprosomatinae) that protect themselves from predators by securing the openings of their shells or cases firmly against the substrate, a behavior we call “cathaptosis.” Common features of cathaptosis in caddisfly larvae include a case with its vulnerable opening oriented parallel with the substrate and accompanied by behavior that grips the substrate, fixing the case opening firmly against it when threatened. We suggest that these defensive strategies have evolved multiple times in Trichoptera, especially in case-making larvae. We demonstrate some examples and provide tentative lists of caddisflies whose larvae may have evolved these defensive strategies.